GW24-e1002 Advanced glycation end products induces apoptosis and shorts telomere length in human adipose tissue-drived stem cells through modulation of MAPK pathways. (1st October 2013) - Feng, Wu; Zhiqing, He; Ruizhen, Ji; Xin, Wang; Zonggui, Wu; Chun, Liang
Abstract : Objectives: To investigate the effects of advanced glycation endproducts (AGEs) on apoptosis and telomere length of human adiposetissue-derived stem cells (ADSCs) and the related molecular mechanism. Methods: ADSCs were obtained by combination with enzymaticallydigestion and centrifugation, and then were identified to observe cultured cells' morphology, induce differentiation towards adipocytes, osteocytes andchondrocytes, and determine by fluorescence activated cell sorter (FACS) analysis. The cells were exposed to AGE-HSA (concentration of 0, HSA 200, 10, 50, 100, 200 μg/ml) for 24 hours. The apoptotic rates were investigated by AnnexinV-FITC Apoptosis Detection Kit and Caspase-Glo™ 3/7 Assay. Telomere lengths were measured byquantitative PCR. The expression of RAGE, p-EPK1/2, p-p38 MAPK, p-JNK1/2 and caspase3 was determined by western blot. Then the cells were preincubated with ERK, p38 and caspase3 inhibitors before the stimuli, the apoptosis and telomerelength of ADSCs were evaluated once more. Results: Compared with the 200μg /ml HSA group, AGE-HSA (50, 100, 200 μg/ml) could significantly inhibit the apoptosis, short telomere length, decrease phosphorylation-ERK1/2 (p-ERK1/2), and increase p-p38MAPK, but do not affect expressions of p-JNK1/2 in ADSCs. Moreover, treatment of ADSCs with 100μg/ml AGE-HSA resulted in activation of caspase-3. Furthermore, PD98059 (ERK1/2 inhibitor) significantly enhanced AGE-HSA induced apoptosis and shortened telomere length in ADSCs, whereas caspase-3 inhibitor or SB203580 (p-p38MAPK inhibitor), decreased apoptosis and longer telomere length in ADSCs. Conclusions: AGE-HSA could promoted the apoptosis and shortened telomere length in ADSCs via of activation of RAGE-MAPK-Caspase3 pathway. These findings partly revealed a novel mechanism about telomere length participating in the dysfunction of ADSCs induced by AGE-HSA.